Impact of Anganwadi Workers’ Soft Skills on Anganwadi Children’s Developmental Milestones (Indian Journal of Extension Education, 2023)
A study was conducted in urban and rural anganwadi centers (AWC), to assess the soft skills such as communication skills, time management, positive attitude, and teamwork of anganwadi workers (AWW) as well as how this relates to the children’s developmental milestones. 60 AWW from 30 rural and 30 urban AWC and five 3-6-year-old children from each AWC by random sampling were chosen. There was a significant difference in communication skills, positive attitude, and teamwork. Gross motor skills of rural children were found significantly higher than in urban children and language skills were significantly higher in urban children rather than rural children. Teamwork of AWW was found positively correlated with cognitive skills and socio-emotional skills. It was imperative that need-based training programmes for AWWs, including early childhood education and other training initiatives, focus on improving soft skills of preschool education and developmental milestones can be maintained.